2019
DOI: 10.14412/2074-2711-2019-2-30-36
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility-weighted MR imaging (SWI) of basal ganglia iron deposition in the early and advanced stages of Parkinson's disease

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease and the first one among the nosological entities of parkinsonism. Susceptibility-weighted imaging (SWI), magnetic resonance imaging (MRI) pulse sequence, which allows the in vivo estimation of the values of iron deposition in different areas of the brain, is a potential technique for the early diagnosis of PD and for the study of the pathogenesis of its complications.Objective: to compare the values of iron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the junction area between the central area and the peripheral zone, T2WI is mainly used. When the benign and malignant cannot be determined, DWI sequence is supplemented [ 7 ]. Peeters et al believe that according to the clinical stage obtained by MRI and the GS score obtained by the pathological results of biopsy tissue, the condition of patients with PCA can be evaluated comprehensively and accurately [ 8 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the junction area between the central area and the peripheral zone, T2WI is mainly used. When the benign and malignant cannot be determined, DWI sequence is supplemented [ 7 ]. Peeters et al believe that according to the clinical stage obtained by MRI and the GS score obtained by the pathological results of biopsy tissue, the condition of patients with PCA can be evaluated comprehensively and accurately [ 8 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In-vivo models have furthered our understanding of these environmental agents, revealing increased iron deposition in subcortical brain structures following mitochondrial impairment (Mochizuki et al 1994 ). Subcortical brain iron deposition in PD has been extensively studied using neuroimaging and post-mortem brain examinations (Zhang et al 2010 ; Trufanov et al 2019 ; Barbosa et al 2015 ; Wang et al 2016 ). Histopathological investigations have demonstrated that iron deposition is mainly localized to the mitochondria on a subcellular level, stressing the importance of this organelle in regulating intracellular iron metabolism (Muñoz et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…5 Subcortical brain iron deposition in PD has been extensively studied using neuroimaging and post-mortem brain examinations. [6][7][8][9] Histopathological investigations have demonstrated that iron deposition is mainly localized to the mitochondria on a subcellular level, stressing the importance of this organelle in regulating intracellular iron metabolism. 2 Mitochondria are responsible for the macromolecular iron integration in metalloproteins, Fe-Sulfur clusters, or heme groups.…”
Section: Introductionmentioning
confidence: 99%